Mental distress and "self-stigma" in the context of support provision: exploring attributions of self-stigma as sanism. Issue 1 (18th December 2019) - Armstrong, Victoria; Brandon, Toby
Abstract : Purpose: The purpose of this paper is to discuss the findings from a detailed qualitative PhD study exploring experiences of stigma and discrimination in the lives of people in receipt of "mental health support" at two voluntary sector organisations in the North East of England. Design/methodology/approach: Empirical material was collected during two periods of three-month long ethnographic periods of fieldwork from July to December of 2013 at two organisations providing support to their members who experience or have experienced mental distress. Along with field notes taken during and after periods of participant observation, the empirical material also included 30 interviews with staff ( n =10) and members ( n =20) across both organisations, along with a series of three focus groups at each organisation. Findings: Staff at the organisations did not demonstrate obvious stigmatising or discriminatory attitudes or behaviours. However, they did attribute "self-stigma" to particular attitudes and behaviours of some of the members they support, referring to how they "made excuses", "did not try" and/or "avoided situations". Originality/value: This paper argues that these attributions resulted from the misrecognition of members' reactions to experiences of discrimination. The empirical material also suggests that these attributions of self-stigma may be indicative of the material limitations of the support environment, the consequent frustrations of well-intentioned staff, and, overall, as symptoms of neoliberalism. Drawing upon a Mad Studies approach and focussing on self-stigma and its attribution in contemporary mental health support, this paper provides a new perspective, which considers how stigma is linked to discrimination by rethinking what is thought of as "self-stigma".